Temporal Arteritis Revealing Antineutrophil Cytoplasmic Antibody–Associated Vasculitides: A Case–Control Study. Issue 2 (21st December 2020) - Delaval, Laure; Samson, Maxime; Schein, Flora; Agard, Christian; Tréfond, Ludovic; Deroux, Alban; Dupuy, Henry; Garrouste, Cyril; Godmer, Pascal; Landron, Cédric; Maurier, François; le Guenno, Guillaume; et al.
Abstract : Objective: Temporal arteritis (TA) is a typical manifestation of giant cell arteritis (GCA). Antineutrophil cytoplasmic antibody (ANCA)–associated vasculitides (AAVs) are rarely revealed by TA manifestations, leading to a risk of misdiagnosis of GCA and inappropriate treatments. This study was undertaken to describe the clinical, biologic, and histologic presentations and outcomes in cases of TA revealing AAV (TA‐AAV) compared to controls with classic GCA. Methods: In this retrospective case–control study, the characteristics of patients with TA‐AAV were compared to those of control subjects with classic GCA. Log‐rank test, with hazard ratios (HRs) and 95% confidence intervals (95% CIs), was used to assess the risk of treatment failure. Results: Fifty patients with TA‐AAV (median age 70 years) were included. Thirty‐three patients (66%) presented with atypical symptoms of GCA (ear, nose, and throat involvement in 32% of patients, and renal, pulmonary, and neurologic involvement in 26%, 20%, and 16% of patients, respectively). Blood samples were screened for ANCAs at the time of disease onset in 33 patients, and results were positive in 88%, leading to a diagnosis of early TA‐AAV in 20 patients. The diagnosis of AAV was delayed a median interval of 15 months in 30 patients. Compared to controls with GCA, patients with TA‐AAV were younger (median age 70 years versus 74 years), were more frequently men (48% versus 30%), and had high frequencies of atypical manifestations and higher C‐reactive protein levels (median 10.8 mg/dl versus 7.0 mg/dl). In patients with TA‐AAV, temporal artery biopsy (TAB) showed fibrinoid necrosis and small branch vasculitis in 23% of patients each, whereas neither of these characteristics was evident in controls with GCA. Treatment failure–free survival was comparable between early TA‐AAV cases and GCA controls, whereas those with delayed TA‐AAV had a significantly higher risk of treatment failure compared to controls (HR 3.85, 95% CI 1.97–7.51; P < 0.0001). Conclusion: TA‐AAV should be considered diagnostically in cases of atypical manifestations of GCA, refractoriness to glucocorticoid treatment, or early relapse. Analysis of TAB specimens for the detection of small branch vasculitis and/or fibrinoid necrosis could be useful. Detection of ANCAs should be performed in cases of suspected GCA with atypical clinical features and/or evidence of temporal artery abnormalities on TAB.